GEORREFERENCIAMENTO DOS CASOS DE AVC ATENDIDOS NOS TRÊS HOSPITAIS DE REFERÊNCIA PARA NEUROLOGIA DO SISTEMA ÚNICO DE SAÚDE DA CIDADE DE CAMPO GRANDE, MS, 2015 - 2019 - Raquel Luciana Angela Marques Tauro (2022)
Stroke is an epidemic non-transmissible and with a high impact on public health in Brazil. The geographical distribution of the cases has still been little studied in the state of Mato Grosso do Sul. The objective of the present study was to construct a geographical map of the cases of this illness, initiating with the internments the hospitals noted for neurology and neurosurgery of the Unified System of Health (SUS), in the city of Campo Grande (MS), during the period stretching between 2015 and 2019, and identify possible overlapping with maps of socioeconomic factors and health resources. It consists of an observational, descriptive, quantitative and qualitative study, initiating with the secondary data of hospital internments, statistical analysis and the georeferenced of these occurrences. With the determination of the mapping of the occurrence of the stroke and the verification of their geographic superposition, among other factors, such as the density of the health resources, income and index of human development, it was possible to verify the association between the variables so as to offer a subsidy concerning future decision-making in regional public health. The sample consisted of 4895 cases, the majority of patients being male (55.3%), average age of 66 years, 71.7% from Campo Grande. As for health assistance, 77% of the municipalities do not dispose of the organized prehospital service, and these cases obtained positive association with mortality (Chi-square, p<0,0001). The period of hospital internment longer than 15 days was associated with the mortality (Chi-square, p<0,0001). The stroke cases from the capital were distributed in the shape of a “horseshoe” in the poorer revenue neighborhoods. The occurrences in the cities of the interior in their majority were from cities more than 100km from Campo Grande (83%). The data presented in this study collaborated with the Stroke local epidemiological knowledge and revealed lacunae in the offer of timely care to these patients in the cities of the interior of the state, as well as the greater proportion of these cases in the poorer neighborhoods in the city of Campo Grande.